A Conceptual Framework for Analyzing Occupational Safety and Health Program Investment: Hierarchy of Controls-Based Approach - Sudiarno, Adithya; Putri Maharani, Nadira (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: The Frequency Rate (FR) of workplace accidents in 2019 was recorded at 3.4, meaning that for every million work hours, there were 3.4 cases of workplace accidents. In 2020, the FR increased to 3.6, and in 2021, it further rose to 3.8. Therefore, companies need to make improvements to reduce the number of work accidents by investing some resources in the Occupational Safety and Health (OSH) investment program. This study aims to develop a conceptual framework for analyzing the OSH investment program by considering its benefits and costs. Methods: Hierarchy of controls was used in this study to classify and identify OSH programs, OSH investment items, and OSH implementation options. The in-depth interview was also conducted by involving several experts to formulate and justify the items in the conceptual framework. Result: This study resulted in 2 main aspects, namely carefully chosen OSH experts to ensure reliable and relevant information collected and involving a detailed analysis of different data levels (3, 2, and 1) along with a breakdown of costs for each level 1 data. Conclusion: The finding of this study is a conceptual framework to help and direct companies in order to analyze the selection of OSH programs, OSH investment items, and OSH implementation options by prioritizing the hierarchy of controls.